PEMBAKARAN LAHAN UNTUK PEMBUKAAN LAHAN PERKEBUNAN (STUDI PUTUSAN NOMOR 468/PID.B/LH/2021/PN RHL): Land Burning for Opening Plantation Land (Study of Adjudication Number 468/PID.B/2021/PN/RHL) - Farahdiba Hakim; Narita Adityaningrum (Faculty of Law, Universitas Trisakti, 2024)
Forest and land burning incidents are a phenomenon that often occurs in Indonesia. Most people still carry out actions to clear land by burning land. The formulation of the problem is about the suitability of District Court Decision Number 468/Pid.B/Lh/2021/Pn Rhl regarding the case of land burning to clear plantation land with the provisions of UUPPLH and the efforts that must be made by the regional government of Rokan Hilir Regency, Riau Province to overcome land fires plantations in the Rokan Hilir Regency area, Riau Province. This type of research uses normative law which is descriptive analytical and uses secondary data which is analyzed qualitatively by drawing deductive conclusions. Research results and discussion and hhe conclusion is that the District Court Decision Number 468/Pid.B/Lh/2021/Pn Rhl is in accordance with the provisions of Article 99 paragraph (1) UUPPLH but according to the author this decision can add Article 69 paragraph (1) letter a as a strengthening article for Article 99 paragraph (1) and Article 69 paragraph (1) letter h UUPPLH. With the Riau Province Regional Regulation Number 1 of 2019, the Riau Regional Government is not prepared enough to monitor technical preparedness measures, other efforts include extinguishing and rehabilitation